Viability of Clostridium difficile in mortadella with added essential oils and reduced sodium nitrite content (Research, Society and Development, 2022)
The effects of additioning essential oil mixtures and reducing the sodium nitrite content (75 ppm) on Clostridium difficile inoculated in mortadellas and on the product’s technological characteristics were evaluated. 15 essential oils were tested preliminarily, but only four were selected. The minimum bactericidal concentrations found were 1.2 % for Ocimum basilicum, 0.3 % for Origanum vulgare and for Thymus vulgaris and 0.15 % for Litsea cubeba. There wasn`t significant difference in viable cell growth between treatments and the control; however, there was an increase in viable cells of approximately 2.5 log10 MPN/g after the fifth day. Combinations of oils didn`t prevent sporulation, however a synergistic effect was observed in vitro. There was a reduction in pH during storage and a greater amount of residual nitrite for the F1 treatment (Origanum vulgare (0.2 %); Thymus vulgaris (0.05 %) and Litsea cubeba (0.025 %), with 10.23 ppm, and reduction of residual nitrite during the storage period from 18.75 ppm on the first day of storage to 5.11 ppm on the last. No significant changes were observed in the technological characteristics of the product with the analyzed treatments.